2010
DOI: 10.20886/jpsek.2010.7.2.93-100
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Finansial Pengelolaan Agroforestri Dengan Pola Sengon Kapulaga Di Desa Tirip, Kecamatan Wadaslintang, Kabupaten Wonosobo

Abstract: Agroforestry is a land-use technique that has been mostly done by farmers in Indonesia. In addition to providing a continuous outcome, it is also good to preserve the environment. This reseearch village of Tirip, Wadaslintang sub district, Wonosobo Distric. This research was descriptive qualitative and quantitative through primary and secondary data collection. The method used was by mean of interviewing respondents and data collected were use to analyzed the financial analysis with the 9-year cycle and the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 0 publications
1
5
0
7
Order By: Relevance
“…This will have an impact on efforts to increase farmers' capacity. This condition is consistent with findings of Kusumedi and Jariyah (2010); Premono and Lestari (2013), and Suherdi et al (2014) who reported that agroforestry farmers generally graduated from elementary and junior high schools. This is in line with Winata and Yuliana (2012) who stated that in agroforestry, forest farmers are well highly educated, they only have farming experience that has been with them since a young age.…”
Section: Results and Discussion A Individual Characteristics Of supporting
confidence: 90%
“…This will have an impact on efforts to increase farmers' capacity. This condition is consistent with findings of Kusumedi and Jariyah (2010); Premono and Lestari (2013), and Suherdi et al (2014) who reported that agroforestry farmers generally graduated from elementary and junior high schools. This is in line with Winata and Yuliana (2012) who stated that in agroforestry, forest farmers are well highly educated, they only have farming experience that has been with them since a young age.…”
Section: Results and Discussion A Individual Characteristics Of supporting
confidence: 90%
“…Peralatan yang digunakan oleh petani diasumsikan sebagai barang habis pakai, sehingga tidak diperhitungkan biaya penyusutannya. Analisis kelayakan finansial usaha tani telah banyak dilakukan pada pola agroforestri untuk mengetahui kelayakan usaha agroforestri tersebut, misalnya pada agroforestri sengon kapulaga (Indrajaya & Sudomo, 2013;Kusumedi & Jariyah, 2010), jabon kapulaga (Indrajaya & Siarudin, 2015), dan agoforestri pada beberapa jenis tanaman bawah (Nadeak, Qurniati, & Hidayat, 2014).…”
Section: B Pengumpulan Dan Analisis Dataunclassified
“…Agroforestri banyak diadopsi oleh petani di Indonesia karena merupakan teknik penggunaan lahan yang sangat cocok untuk dilakukan di lahan yang sempit (pekarangan) dan tegalan (lahan kering) (Kusumedi dan Jariyah, 2010). Hasil yang didapatkan berkelanjutan, produk jangka pendek berupa produk non kayu (perkebunan/pertanian) dan produk kayu sebagai hasil jangka panjang.…”
Section: Hasil Dan Pembahasan Keanekaragaman Jenis Tumbuhan Bawahunclassified